Perbedaan Kadar Bilirubin Pada Neonatus Yang Mengalami Dan Tidak Mengalami Inkompatibilitas ABO - Galuh Haryaninggar; Reni Wahyu Triningsih; Asworoningrum Yulindahwati (Jurnal Informasi Kesehatan Indonesia (JIKI), 2017)
with and without ABO incompatibility in RSIA Puri, Malang. The design study is an analyticretrospective comparative approach. The population of 85 newborns with ABO incompatibility and141 newborns without ABO incompatibility in RSIA Puri, Malang. Samples taken by proportionatestratified random sampling. The measurement results show that the average blood level of bilirubin innewborns with ABO incompatibility of 10.89 mg / dL, while in newborns without ABO incompatibility of9.04 mg / dL then the data were analyzed by Independent T-test with dk = 169 , showed a significantvalue (0.000) < alpha (0.05) so it can be concluded that there are differences in levels of bilirubin(total) of blood between newborns with and without ABO incompatibility